High- or low-risk prisoner, high- or low-risk ex-offender? Assessing the predictive validity of the level of service/risk-need-responsivity (LS/RNR) instrument among different subgroups of Danish prisoners - Larsen, Britt Østergaard (European journal of criminology, 2025)
The use of risk assessment tools such as the level of service/risk-need-responsivity (LS/RNR) has spread in criminal justice systems across the world. Although risk assessments have been implemented in many European jurisdictions, there is still a need for empirical knowledge on the applicability of the instruments in these geographical contexts. In this study, we follow the first cohorts of Danish prisoners who were assessed with LS/RNR (N?=?4075) and evaluate the predictive validity of recidivism within 24 months from prison release. The results suggest that LS/RNR is a medium-strong predictor of recidivism when evaluated with standard methods. However, we also find large differences in recidivism outcomes between subgroups (defined by age and minority background) within identical risk levels, and we discuss the implications of these findings for research and practice.